2005
DOI: 10.1111/j.1744-6570.2005.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Pay Satisfaction and Organizational Outcomes

Abstract: Using multi level and multi method data, we investigated the relationship between pay satisfaction and outcomes at the organizational level of analysis. Individual‐level survey data on pay satisfaction (including satisfaction with pay level, satisfaction with pay structure, satisfaction with pay raises, and benefits) were collected from 6,394 public school teachers. Organizational‐level outcome data, both survey and archival, were collected from the 117 public school districts employing these teachers. With re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
190
0
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(212 citation statements)
references
References 60 publications
8
190
0
10
Order By: Relevance
“…The correlation between our measures of SV and the economic value of concessions was relatively small (r ϭ .20, p Ͻ .10), 5 which is comparable to Curhan et al's (2006) correlation of .16 between total SV and economic value on a laboratory task in which economic value was objectively verifiable. This is also consistent with Currall et al's (2005) finding that objective pay levels did not correlate with pay satisfaction and Dreher et al's (1988) finding of a relationship between fringe benefit levels and satisfaction with these benefits only among participants who were knowledgeable about how their benefit levels compared with those of other employers in the same industry.…”
Section: Measures Subjective and Economic Value (Employment Survey)supporting
confidence: 88%
See 1 more Smart Citation
“…The correlation between our measures of SV and the economic value of concessions was relatively small (r ϭ .20, p Ͻ .10), 5 which is comparable to Curhan et al's (2006) correlation of .16 between total SV and economic value on a laboratory task in which economic value was objectively verifiable. This is also consistent with Currall et al's (2005) finding that objective pay levels did not correlate with pay satisfaction and Dreher et al's (1988) finding of a relationship between fringe benefit levels and satisfaction with these benefits only among participants who were knowledgeable about how their benefit levels compared with those of other employers in the same industry.…”
Section: Measures Subjective and Economic Value (Employment Survey)supporting
confidence: 88%
“…However, SV and economic value tend to be only weakly correlated (e.g., Curhan et al, 2006;Galinsky et al, 2002), and there are theoretical arguments and empirical data suggesting that attitudes and behavioral intentions are better predicted by SV than economic value (e.g., Curhan et al, 2006). Further, objective pay levels do not always correlate with pay satisfaction (Currall, Towler, Judge, & Kohn, 2005), which supports the idea that subjective perceptions can be more proximal to generalized job attitudes than can economic characteristics.…”
Section: Turnover Intentionmentioning
confidence: 91%
“…Research results have shown job dissatisfaction to be associated with negative behavioral outcomes such as absenteeism, workplace accidents, and labor turnover (Griffeth, Horn, & Gaertner, 2000;Hellman, 1997;Hellriegel & Slocum, 2004;Newstrom, 2006;Sousa-Poza & Sousa-Poza, 2007). Currall et al, (2005) found pay satisfaction to be positively related to performance and negatively related to employee turnover intentions. Similarly, the results of another study by Davis (2006) also showed general job satisfaction to be strongly and negatively related to turnover intentions (r = -.69).…”
Section: Continuance Commitmentmentioning
confidence: 99%
“…Some studies indicated that job satisfaction is connected with teachers' sense of efficacy (Currall, Towler, Judge, & Kohn, 2005). Therefore, when teachers have high perception of their professional job quality, they also have positive attitudes towards teaching, as an achievement factor.…”
Section: Literature Reviewmentioning
confidence: 99%